(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aims to investigate the factors contributing to the purchase of electric vehicles (EVs) in India. As the Indian government encourages the adoption of sustainable transportation, understanding the key factors influencing consumer purchase decisions is crucial for accelerating the transition to electric mobility. This research explores various factors that shape purchase intentions for EVs, including environmental considerations, cost savings, range and charging infrastructure, performance and technology, government policies and incentives, and social influence. Moreover, the study uncovers the importance of technology and performance features in influencing consumer decisions. Consumers value advanced features, such as regenerative braking and connectivity options, which contribute to a superior driving experience. Social influence, including peer recommendations and positive experiences shared by existing EV owners, also emerges as an influential factor